2021
DOI: 10.1002/smll.202103773
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Prepared Water‐Resistant Organic–Inorganic‐Hybrid Perovskite Quantum Dots with Zn–Oxygen Vacancies for Attempts at Nitrogen Fixation

Abstract: Applying organic–inorganic hybrid perovskite quantum dots (PQDs) to photocatalytic nitrogen fixation is hindered long‐term by the inherent instability in water and tedious preparations. Here, to realize PQD‐catalyzed photocatalytic N2 reduction reaction (NRR), water‐resistant PQDs are simply prepared through one‐step electrospray synthesis in microseconds. During the fast electrospray, PQDs of Zn/PbO‐doped methylammonium lead bromide (Zn/PbO/PC–Zn/MAPbBr3, MA: CH3NH3) are prepared and part‐encapsulated by poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…+ with the coupling constant of 52.2 Hz when 14 N 2 gas was introduced, whereas the isotopic labeled item showed the doublets of 15 NH 4 + with the coupling constant of 73.1 Hz when using 15 N 2 gas. [49] These results verified that the generated NH 4 + indeed originated from the feeding N 2 .…”
Section: Photocatalytic N 2 Reduction Performancesupporting
confidence: 61%
“…+ with the coupling constant of 52.2 Hz when 14 N 2 gas was introduced, whereas the isotopic labeled item showed the doublets of 15 NH 4 + with the coupling constant of 73.1 Hz when using 15 N 2 gas. [49] These results verified that the generated NH 4 + indeed originated from the feeding N 2 .…”
Section: Photocatalytic N 2 Reduction Performancesupporting
confidence: 61%
“…Gao et al. [ 183 ] used organic–inorganic hybrid perovskite QDs for photocatalytic NRR in solution without sacrificial agents. Perovskite QDs of Zn‐PbO‐doped methylammonium lead bromide (Zn‐PbO/polycarbonate/Zn‐CH 3 NH 3 PbBr 3 ) maintained favorable water resistance.…”
Section: Semiconducting Qds For Energy Conversionmentioning
confidence: 99%
“…171 While earlier studies were focused on the Cs-based 172,173 or MA-based 174,175 perovskites for the Pb-Sn mixed composition, FAPb 1Àx Sn x Br 3 NCs 176,177 have also gained momentum recently, along with partial Pb replacement by other metals in the perovskite structure. [178][179][180][181] Cai et al reported the facile synthesis of FAPb 1Àx Sn x Br 3 NCs at RT using a modified LARP approach. 155 They found that the crystal structure remained cubic until 50% of Pb had been replaced by Sn; however, on further increasing the Sn concentration, the cubic phase partially lost its high symmetry structures.…”
Section: Composition Engineeringmentioning
confidence: 99%